368 REVEAL: Phase 1 dose-escalation study of NKTR-262, a novel TLR7/8 agonist, plus bempegaldesleukin: local innate immune activation and systemic adaptive immune expansion for treating solid tumors. (10th December 2020) - Diab, Adi; Curti, Brendan; Bilen, Mehmet; Brohl, Andrew; Domingo-Musibay, Evidio; Borazanci, Erkut; Fanton, Christie; Haglund, Cat; Vimal, Mona; Muhsin, Mann; Marcondes, Mario; Nguyen, Anh; et al.
Abstract : Background: NKTR-262 is a small-molecule agonist of toll-like receptors (TLR) 7/8. Given by intratumoral (IT) injection, NKTR-262 is retained within the tumor microenvironment (TME) and promotes an immunostimulatory milieu and tumor antigen release. Bempegaldesleukin (BEMPEG) is a CD122-preferential IL-2 pathway agonist, which increases proliferation and tumor infiltration of CD8 + T cells and natural killer (NK) cells. Preclinically, NKTR-262 plus BEMPEG combined innate immune signaling and enhanced antigen presentation, with sustained T-cell activation, resulting in tumor growth inhibition of treated and abscopal lesions. Methods: This phase 1 dose-escalation study enrolled patients with relapsed/refractory, advanced/metastatic solid tumors (REVEAL; NCT03435640 ). Patients received escalating doses of NKTR-262 (0.03 mg to 3.84 mg IT) followed 3 weeks' later by BEMPEG (0.006 mg/kg IV) q3wk utilizing a 3+3 design. The primary endpoint was safety and tolerability, including definition of the recommended phase 2 dose (RP2D). Other endpoints included antitumor activity, pharmacodynamics, and pharmacokinetics. Results: As of June 15, 2020, 36 patients were enrolled. One dose-limiting toxicity, transient transaminase elevation, was observed at the highest NKTR-262 dose (3.84 mg). The most frequent treatment-related adverse events were flu-like symptoms, fatigue, nausea, and pruritus, consistent with the known profile of BEMPEG. Early evidence of clinical activity was observed in patients with metastatic melanoma, with a disease control rate (partial response [PR] + stable disease) of 41.2% (7/17 patients), including two patients with PRs after progression on two prior immunotherapy regimens. Preliminary analyses showed dose-dependent induction of CXCL10 and type 1 interferon genes, consistent with TLR7/8 engagement. CD11c + target cells were significantly more abundant in baseline melanoma biopsies than other tumor types (p<0.001). Induction of TLR7/8-responsive genes correlated with CD11c + baseline density (p<0.05). Minimal TLR7/8-dependent changes in immune cell subsets or inflammatory cytokines were observed in peripheral blood, reflecting favorable TME modifications driven by retention of NKTR-262. Increased activation of CD4 +, CD8 +, and NK cells in blood were observed, consistent with BEMPEG mechanism of action. Conclusions: NKTR-262 plus BEMPEG led to engagement of the entire immune activation cascade required for systemic tumor clearance. Robust TLR7/8 engagement supported the NKTR-262 mechanism of action, while the minimal toxicity profile underscored the benefit of local delivery of NKTR-262, and the BEMPEG combination induced systemic activation of T and NK cells. These data support the RP2D of NKTR-262 (3.84 mg IT) plus BEMPEG (0.006 mg IV) q3w, and the initiation of the phase 1b dose-expansion phase, which is exploring concurrent dosing, with or without nivolumab, in relapsed/refractory metastatic melanoma patients. Trial Registration: NCT03435640 Ethics Approval: The study was approved by the institutional review board of each participating site.